2016
DOI: 10.1108/ccij-05-2015-0025
|View full text |Cite
|
Sign up to set email alerts
|

Communicative leadership

Abstract: Purpose – The purpose of this paper is to enhance the knowledge of how leadership concepts are embraced by leadership actors and perceived to influence relationships between leaders and co-workers. Specifically, the authors aim to investigate how leaders and co-workers discursively construct the concept of “communicative leadership” and its practices and perceive that communicative leadership influences relationships, work processes, and agency. Design/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…The other research group relates to examining and defining the characteristics of leadership in public relations. Summarizing the results of these studies, it may be concluded that public relations require leadership with: strategic orientation (Meng & Berger, 2013;Luo & Jiang, 2014;Luo et al, 2015), human orientation and support (Gambetti & Biraghi, 2015;Martinelli & Erzikova, 2017), ethical orientation (Meng & Berger, 2013), professional competencies (Killingsworth & Flynn, 2016), and the ability to achieve quality communication (Meng & Berger, 2013;Hamrin, 2016;Hamrin et al, 2016;Gambetti & Biraghi, 2015). These references, in fact, indirectly show that transformational leadership and ethical leadership behaviour are desirable leadership styles in public relations at the level of PR departments.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The other research group relates to examining and defining the characteristics of leadership in public relations. Summarizing the results of these studies, it may be concluded that public relations require leadership with: strategic orientation (Meng & Berger, 2013;Luo & Jiang, 2014;Luo et al, 2015), human orientation and support (Gambetti & Biraghi, 2015;Martinelli & Erzikova, 2017), ethical orientation (Meng & Berger, 2013), professional competencies (Killingsworth & Flynn, 2016), and the ability to achieve quality communication (Meng & Berger, 2013;Hamrin, 2016;Hamrin et al, 2016;Gambetti & Biraghi, 2015). These references, in fact, indirectly show that transformational leadership and ethical leadership behaviour are desirable leadership styles in public relations at the level of PR departments.…”
Section: Introductionmentioning
confidence: 94%
“…Viewed from the perspective of employees, communicative leadership has significant advantages over authoritative leadership (Hamrin, 2016). Viewed from the perspective of enhancing co-worker agency, communicative leadership should include: facilitating autonomy, sharing responsibility, mutual participation, responsiveness and dialogue (Hamrin et al, 2016). Gambetti and Biraghi (2015) highlight the importance of the humanistic nature of the corporate communications officer as well as conversational leadership.…”
Section: Covenant Leadership In Public Relationsmentioning
confidence: 99%
“…Therefore, future research may use a longitudinal research design and research may use contemporary techniques such as neural networks and/or fuzzy sets to yield robust findings. However, a qualitative study along with a quantitative study can bring additional insight, particularly on the role of internal communication that what constitutes leader–subordinates communication and causes an increase in subordinates' engagement and other productive behaviors such as empowerment, voice (Allert and Chatterjee, 1997; Hamrin, 2016; Hamrin et al. , 2016) etc.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Whilst post-heroic leadership is positioned as the antithesis of heroic leadership, in practice there is much overlap between the two conceptualizations of individual (heroic) and collaborative or shared (post-heroic) leadership, with leaders demonstrating both individualistic and shared characteristics (Crevani et al, 2007; Hamrin et al, 2016; Harding, 2014). For example, in certain situations leaders perform both heroic and post-heroic leadership or hybrid forms of leadership that draw on both sets of attributes (Arnulf et al, 2012).…”
Section: Theoretical Framingmentioning
confidence: 99%